Some ecophysiological characteristics of two dipterocarp species (Shorea curtisii Dyer ex-king and S. leprosula Miq) of potential in regenerating hill dipterocarp forests - Awang, Kamis; Shakri, Ahmad (1985)
The paper report on three experiments to investigate the effects of topography, soils from three topographic positions, moisture supply and shade on the growth of Shorea curtisii Dyer ex-King and S. leprosula Miq seedlings. S. curtisii grew better on the ridge than on the lower slope, where its growth was slower than that of S. leprosula. In contrast, the reverse was true with S. leprosula. Abundant moisture supply was responsible for the relatively slower growth of S. curtisii on the lower slope. In contrast, abundant moisture supply promoted the growth of S. leprosula. Heavy shading suppressed the growth of both species. The data presented also emphasize the need to carefully consider the ecophysiological characteristics of the species in the regeneration of hill dipterocarp forests.